2023
DOI: 10.1007/s13187-022-02247-8
|View full text |Cite
|
Sign up to set email alerts
|

Summer Clinical Oncology Research Experience (SCORE) Program: Engaging Undergraduates from Diverse Backgrounds in Cancer Research

Abstract: Diversifying the future cancer research workforce requires that students engage in cancer research, persist in paths toward science, technology, engineering, mathematics, and medicine (STEMM) fields, and choose cancer research careers. The Summer Clinical Oncology Research Experience (SCORE) Program at Memorial Sloan Kettering, designed in 2010 to engage undergraduate (U) and post-baccalaureate (PB) students from diverse backgrounds in cancer research, is an 8-week summer program pairing an U or PB student wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Other programs, on an institutional level, such as at the University of Arkansas for Medical Sciences, have found that URM students can benefit from research‐focused STEMM summer programs, with most participants maintaining contact with their mentor following the program's conclusion (Prince et al, 2023). For medical‐focused programs, Summer Clinical Oncology Research Experience at Memorial Sloan Kettering had 98% of students progress toward higher STEMM degree fields, with 54% of participants having co‐author publications (Liberman et al, 2023). Beyond this, STEMM summer bridge programs, while similar, are distinct in often focusing on adjustment to college and have been extensively reviewed previously (Ashley et al, 2017; Bradford et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other programs, on an institutional level, such as at the University of Arkansas for Medical Sciences, have found that URM students can benefit from research‐focused STEMM summer programs, with most participants maintaining contact with their mentor following the program's conclusion (Prince et al, 2023). For medical‐focused programs, Summer Clinical Oncology Research Experience at Memorial Sloan Kettering had 98% of students progress toward higher STEMM degree fields, with 54% of participants having co‐author publications (Liberman et al, 2023). Beyond this, STEMM summer bridge programs, while similar, are distinct in often focusing on adjustment to college and have been extensively reviewed previously (Ashley et al, 2017; Bradford et al, 2021).…”
Section: Introductionmentioning
confidence: 99%